2020
DOI: 10.1080/20008198.2020.1753938
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and comorbidity of the ICD-11 and DSM-5 for PTSD caseness with previous diagnostic manuals among the Japanese population

Abstract: Background: The diagnostic criteria for posttraumatic stress disorder (PTSD) differ between DSM-5 and ICD-11, which may affect the estimation of prevalence. Objective: To investigate the concordance of ICD-11 and DSM-5, as compared to ICD-10 and DSM-IV, regarding PTSD caseness among Japanese people who had experienced different potentially traumatic events. In addition, we estimated the comorbidity with major depressive disorder and generalized anxiety disorder according to these four diagnostic manuals. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…For future crosscultural studies, it would be valuable to include measurements on culture orientations (Olff et al, 2019). Future accumulation of data may reveal areas of commonality (Ho et al, 2020;Kameoka et al, 2020;Oe, Ito, Takebayashi, Katayanagi, & Horikoshi, 2020) and differences with Western results.…”
Section: Discussionmentioning
confidence: 99%
“…For future crosscultural studies, it would be valuable to include measurements on culture orientations (Olff et al, 2019). Future accumulation of data may reveal areas of commonality (Ho et al, 2020;Kameoka et al, 2020;Oe, Ito, Takebayashi, Katayanagi, & Horikoshi, 2020) and differences with Western results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the probability of co-diagnosis with PTSD is relatively high, especially in depression (Afzali et al 2017). It is noteworthy that compared to the DSM-5 diagnostic criteria, the ICD-11 diagnostic criteria showed lower rates of comorbidity, especially with depression and anxiety disorders (e.g., Wisco et al 2017, Oe et al 2020. For example, Shevin et al (2018) reported that 27.4% of the participants who met the diagnostic criteria of DSM-5 PTSD also met anxiety disorders and depression criteria.…”
Section: Diagnosis and Diagnostic Criteriamentioning
confidence: 99%
“…Several studies showed that using the ICD-11 and DSM-5 criteria provided equivalent comorbidity rates between PTSD and other mental disorders such as major depression disorder (MDD) [e.g., ( 10 , 11 )] and generalized anxiety disorder (GAD) ( 11 ). However, other studies showed that the DSM-5 could significantly increase the co-occurrence rate [e.g., ( 12 , 13 )]. In addition, Shevlin et al ( 9 ) reported a lower co-occurring rate with MDD and GAD for DSM-5 criteria.…”
Section: Introductionmentioning
confidence: 99%